2016
DOI: 10.1111/jcpp.12633
|View full text |Cite
|
Sign up to set email alerts
|

Rumination in dysphoric mothers negatively affects mother–infant interactions

Abstract: This study suggests that the repetitive, internal focus of a ruminative state is causally implicated in mother-infant interaction quality, regardless of the level of depressive symptoms. This research extends understanding of specific mechanisms involved in the quality of the mother-infant relationship.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 36 publications
0
21
0
Order By: Relevance
“…It is possible that some mothers may have the capacity to provide sensitive care for short intervals but struggle to maintain sensitivity across longer interactions with their infants. Although previous studies have found that maternal sensitivity decreases over time in the context of increasing infant distress during laboratory-based stressors Conradt & Ablow, 2010;Tester-Jones et al, 2016), no study has previously investigated parents' ability to sustain sensitivity during naturalistic play interactions with their infants.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…It is possible that some mothers may have the capacity to provide sensitive care for short intervals but struggle to maintain sensitivity across longer interactions with their infants. Although previous studies have found that maternal sensitivity decreases over time in the context of increasing infant distress during laboratory-based stressors Conradt & Ablow, 2010;Tester-Jones et al, 2016), no study has previously investigated parents' ability to sustain sensitivity during naturalistic play interactions with their infants.…”
Section: Introductionmentioning
confidence: 98%
“…These effects are also apparent among postpartum women (Insana, Williams, & Montgomery-Downs, 2013;Mcbean, Kinsey, Montgomery-downs, & Virginia, 2016;McBean & Montgomery-Downs, 2013;Swain, O'Hara, Starr, & Gorman, 1997). In the broader literature on the antecedents of caregiving behavior, maladaptive functioning in each of these domains has been linked to less positive maternal behavior toward children (Crandall, Deater-Deckard, & Riley, 2015;Leerkes, 2011;Sturge-Apple, Jones, & Suor, 2017;Tester-Jones, Karl, Watkins, & O'Mahen, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Apart from the negative association between rumination and parental mental health, DeJong, Fox, and Stein (2016) suggested that rumination can affect a mother's responsiveness to her infant due to reduced cognitive control and cognitive biases. Indeed, studies have found that maternal rumination is associated with reduced maternal responsiveness (Stein, Lehtonen, Harvey, Nicol-Harper, & Craske, 2009;Stein et al, 2012) and sensitivity (Tester-Jones, Karl, Watkins, & O'Mahen, 2017) during motherinfant interactions.…”
mentioning
confidence: 99%
“…Contrary to our expectations, analyses revealed that mothers with a strong tendency to engage in RNT displayed contingent behavior as frequently as mothers with a weak tendency to engage in RNT. These findings provide novel insights insofar as previous studies (Stein et al, 2012;Tester-Jones et al, 2017) assessed the effect of RNT on mother-infant interaction while mothers did versus did not engage in RNT at the time of the assessment. These previous studies left open the question of whether RNT, if it happens frequently, leaves an enduring trace in the quality of how mothers respond to their infants' communicative signals.…”
Section: Discussionmentioning
confidence: 73%
“…Again, this suggests that RNT might influence parenting behavior in women affected by mental disorders. Of note, however, a recent study by Tester-Jones, Karl, Watkins, and O'Mahen (2017) suggested that RNT is a causal factor for changes in mother–infant interactions independent of the diagnostic status of a mother. In this study, dysphoric and non-dysphoric mothers were either induced to engage in RNT or to think about a recent concern that they had managed to resolve.…”
mentioning
confidence: 99%